Rationally designed CdS/Ti3C2 MXene electrocatalysts for efficient CO2 reduction in aqueous electrolyte. Issue 20 (15th October 2021) - Wang, Yuwei; Du, Rong; Li, Zhuo; Song, Haoran; Chao, Zhe; Zu, Daoyuan; Chong, Daotong; Gao, Ningbo; Li, Changping
Abstract: MXene-based catalysts have shown excellent activities in various electrocatalytic reactions due to the two-dimensional structure, good electrical conductivity and abundant surface functional groups. However, because of the competitive reactions in aqueous electrolytes, the application of MXene materials in CO2 electroreduction still remains a challenge. Herein, a simple strategy was developed for the design of high efficient and stable CO2 electroreduction catalysts in aqueous electrolyte. A series of MXene composite catalysts were successfully synthesized by densely coating sulfur vacancy-rich CdS nanoparticles on Ti3 C2 . The two-dimensional MXene skeleton with good conductivity delivers fast electron transfer, improves the electrolyte infiltration and increases the electrochemical surface area. CdS nanoparticles with abundant sulfur vacancies are attached on Ti3 C2 MXene surface, providing active sites for CO2 reduction. Faraday efficiency of the by-product hydrogen could be significantly reduced by minimizing the surface-exposed Ti of the catalyst. Benefited from these merits, the optimal CdS/Ti3 C2 possesses fast CO2 electroreduction reaction kinetics, exhibiting a high CO Faraday efficiency of 94% at -1.0 V vs. reversible hydrogen electrode. This work provides a feasible pathway for the design of MXene-based catalysts of CO2 electroreduction. Graphical abstract: Image 1 Highlights: MXene-based catalysts are applied in aqueous electrolyte system CO2 ERR. The H2 Faradaic efficiency can be controlled by adjusting the surface-exposed Ti. The sulfur vacancy improves CO2 ERR property of CdS/Ti3 C2 nanocomposite. CO Faraday efficiency of the electrocatalyst reaches up to 94% at -1.0 V vs. RHE.